Climate change, nutrition and Mongolia: A risk profile - UNICEF Mongolia; Food and Agriculture Organization of the United Nations; International Food Policy Research Institute; Ringler, Claudia; Bellisario, Kristen; Fanzo, Jessica; Bromage, Sabri; Perez, Nicostrato; Bater, Jorick; Bakey, A.; Dagys, Kadirbyek; Chimed-Ochir, B.; et al. (Food and Agricultural Organization of the United Nations, 2023)
Mongolia is severely affected by adverse climate change impacts, including substantially higher temperatures that have contributed to increased evapotranspiration and the drying up of the country’s water resources. Moreover, the number and intensity of extreme events--especially droughts--is growing, with largest impacts on the poorer population employed in agriculture. At the same time, nutrition security remains out of reach with the co-existence of multiple forms of malnutrition, including obesity. The Mongolian pastoral culture is important to consider in balancing nutritional requirements, health risks, economics, sustainability of food production, including greenhouse gas emissions. While linkages between climate change and food security are increasingly understood, in particular the direct impacts of climate change on crop yields, associated higher food prices, and increased costs of healthy diets resulting in higher levels of malnutrition, other linkages between climate change and nutrition have been barely studied. Mongolia thus suffers from the syndemic of climate change, obesity and undernutrition, which are three co-occurring and interlinked epidemics. A better and more comprehensive understanding of the linkages between climate change and nutrition is key to developing effective interventions to ensure that Mongolia’s population has access to sufficient, safe and nutritious food despite adverse climate outcomes. Importantly, climate change does not only affect food production but can exacerbate malnutrition by removing food and nutrients in all stages of the food value chain. Finally, given the important contribution of food systems to climate change, nutrition policy in Mongolia should more proactively consider environmental impacts.